History Will Tell: Fidel Castro - Billon, Yves (Zarafa Films, 2009)
Verzio FF Submission Duration: 00:52:00 This famous statement of the leader of the Cuban Revolution is still topical today. Fifty years after he captured Havana, weakened by a long illness, Fidel Castro has had to relinquish power. What will Cuba’s future be once its legendary leader has disappeared? Will the country open up to democracy or remain isolated: the ultimate assessment of Fidel’s era will depend on this choice. As a leader at death’s door, standing before his judges, Castro is faced by the main witness, Commandant Huber Matos. The man who certainly was the Chi's and the Castro brothers’ closest strategist in the Sierra Maestro, the man who was so popular that Fidel thought that he would overshadow him, the man who was sentenced to a twenty-year-long imprisonment for being too revolutionary, reexamines the history of the Cuban Revolution in this documentary, from the attack of the Moncada to the recent transfer of power from Fidel Castro to his brother Raúl.